Muc5b Contributes to Mucus Abnormality in Rat Models of Cystic Fibrosis - Keith, Johnathan D.; Henderson, Alexander G.; Fernandez-Petty, Courtney M.; Davis, Joy M.; Oden, Ashley M.; Birket, Susan E. (Frontiers in Physiology, 2022)
Cystic fibrosis (CF) airway disease is characterized by excessive and accumulative mucus in the airways. Mucociliary clearance becomes defective as mucus secretions become hyperconcentrated and viscosity increases. The CFTR-knockout (KO) rat has been previously shown to progressively develop delayed mucociliary transport, secondary to increased viscoelasticity of airway secretions. The humanized-G551D CFTR rat model has demonstrated that abnormal mucociliary clearance and hyperviscosity is reversed by ivacaftor treatment. In this study, we sought to identify the components of mucus that changes as the rat ages to contribute to these abnormalities. We found that Muc5b concentrations in the airway were increased in the KO rat compared to WT, and that Muc5b concentration was directly related to the viscosity of the mucus. Additionally, we found that methacholine administration to the airway exacerbates these characteristics of disease in the KO, but not WT rat trachea. Lastly we determined that at 6 months of age, CF rats had mucus that was adherent to the airway epithelium, a process that is reversed by ivacaftor therapy in the hG551D rat. Overall, these data indicate that accumulation of Muc5b initiates the muco-obstructive process in the CF lung prior to infection.